Impacto de la canasta transfronteriza en la rentabilidad de las empresas comercializadoras de electrodomésticos en la ciudad de Tulcán en el año 2016 - Pilay Vaque, Josué Abraham (2017)
The main objective of this work is to determine the impact of cross-border basket on the profitability of the sales companies of electrical appliances in the city of Tulcán during the year of 2016. This study is based on the initial diagnosis of cross-border basket covered by resolution 039 – 2015 of the Foreign Trade Committee, adopted as a driving mechanism of the economy of the Tulcán city, since, according to the tariff resolution enacted, led to know that 3739 taxpayers are benefited from this resolution and 23 are taxpayers dedicated to sale household appliances which are the population subject to study. The research project has been focused on quantitative data, based on financial information, with results obtained from surveys, collecting economic data for traders….